2002
DOI: 10.1016/s0212-6567(02)79129-4
|View full text |Cite
|
Sign up to set email alerts
|

El Proyecto BIFAP: Base de datos para la Investigación Farmacoepidemiológica en Atención Primaria

Abstract: If BIFAP were viable, a standardised procedure for its use and protocols to support it as a research tool would be put in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The HSD database is very similar to other Primary Care databases: for instance, in the UK, the Clinical Practice Research Datalink (CPRD, formerly GPRD),13 The Health Information Network (THIN)14 and QResearch;15 in Canada, the Canadian Primary Care Sentinel Surveillance Network (CPCSSN);16 in the Netherlands, the Integrated Primary Care Information database (IPCI);17 in Spain, the database Base de datos para la Investigación Farmacoepidemiológica en Atención Primaria (BIFAP) 18. A common feature of these countries is that the GP serves a well-defined population and is the gatekeeper to secondary care.…”
Section: Introductionmentioning
confidence: 94%
“…The HSD database is very similar to other Primary Care databases: for instance, in the UK, the Clinical Practice Research Datalink (CPRD, formerly GPRD),13 The Health Information Network (THIN)14 and QResearch;15 in Canada, the Canadian Primary Care Sentinel Surveillance Network (CPCSSN);16 in the Netherlands, the Integrated Primary Care Information database (IPCI);17 in Spain, the database Base de datos para la Investigación Farmacoepidemiológica en Atención Primaria (BIFAP) 18. A common feature of these countries is that the GP serves a well-defined population and is the gatekeeper to secondary care.…”
Section: Introductionmentioning
confidence: 94%
“…Each of the 17 regions has its own Health Service, which is the administrative and management body responsible for health centers, services and facilities in its region. 2 Regional Health Services integrated in the SNS provide universal access to healthcare to the entire Spanish population regardless their income. While regional variation on covered services and practice guidance are allowed, a portfolio of covered services and health benefits for the Spanish population are adopted for the whole SNS.…”
Section: Database Content 21 | Database In the Context Of The Spanmentioning
confidence: 99%
“…BIFAP is a nonprofit program administered and fully financed by the Spanish Agency for Medicines and Medical Devices (AEMPS) that started in 2001 when primary care EMRs where fully implemented throughout Spain. 1 Ten Autonomous Communities are committed to provide data through bilateral agreements (http://bifap.aemps.es).…”
mentioning
confidence: 99%
“…Exploratory analysis had shown that the follow-up of the population captured in the BIFAP database was dynamic and therefore allowed for illustrative examples. The BIFAP-database is a primary care database from the National Health System in Spain [18]. The database is multi-regional.…”
Section: Data Illustration: Bifap Databasementioning
confidence: 99%